2019
DOI: 10.1021/acscatal.9b03588
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of Iminium Salt-Catalyzed C(sp3)–H Amination: Factors Controlling Hydride Transfer versus H-Atom Abstraction

Abstract: Carbon–nitrogen bonds are extremely prevalent in pharmaceuticals, natural products, and other biologically relevant molecules such as nucleic acids and proteins. Intermolecular amination of C­(sp3)–H bonds by catalytic nitrene transfer is a promising method for forging C–N bonds. An organocatalytic approach to nitrene transfer by way of an iminium salt offers a site-selective method for C­(sp3)–H amination. Understanding of this amination mechanism including the nature of the relevant intermediates and the fac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…In addition to the above experimental work, some theoretical studies on the mechanisms of chiral amine synthesis have also been reported [25–28] . Zheng and co‐workers [26] studied Ir catalyzed α‐amidation of 2‐acylimidazoles and demonstrated a significant effect of nitrene insertion.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…In addition to the above experimental work, some theoretical studies on the mechanisms of chiral amine synthesis have also been reported [25–28] . Zheng and co‐workers [26] studied Ir catalyzed α‐amidation of 2‐acylimidazoles and demonstrated a significant effect of nitrene insertion.…”
Section: Introductionmentioning
confidence: 97%
“…[23,24] In addition to the above experimental work, some theoretical studies on the mechanisms of chiral amine synthesis have also been reported. [25][26][27][28] Zheng and co-workers [26] studied Ir catalyzed α-amidation of 2-acylimidazoles and demonstrated a significant effect of nitrene insertion. Sunoj et al [27] investigated the mechanistic insights into asymmetric amination of diazoacetate catalyzed by dirhodium tetra(trifluoro)acetate with chiral SPINOL-phosphoric acid and found a stereo-controlling transition state with cooperative participation of both catalysts.…”
Section: Introductionmentioning
confidence: 99%